High prevalence of fecal carriage of extended spectrum β-lactamase/AmpC-producing Enterobacteriaceae in cats and dogs - Hordijk, Joost; Schoormans, Anky; Kwakernaak, Mandy; Duim, Birgitta; Broens, Els; Dierikx, Cindy; Mevius, Dik; Wagenaar, Jaap A. (Frontiers in Microbiology, 2013)
ESBL/AmpC producing Enterobacteriaceae have been reported worldwide amongst isolates obtained from humans, food-producing animals, companion animals and environmental sources. However, data on prevalence of fecal carriage of ESBL/AmpC producing Enterobacteriaceae in healthy companion animals is limited. This pilot study describes the prevalence of ESBL/AmpC encoding genes in healthy cats and dogs, and cats and dogs with diarrhea. Twenty fecal samples of each group were cultured on MacConkey agar supplemented with 1 mg/L cefotaxime and in LB-enrichment broth supplemented with 1 mg/L cefotaxime, which was subsequently inoculated on MacConkey agar supplemented with 1 mg/L cefotaxime. ESBL/AmpC genes were identified using the Check-Points CT103 micro array kit and subsequently by sequencing analysis. Chromosomal ampC promoter mutations were detected by PCR and sequencing analysis. From the healthy and diarrheic dogs, respectively 45% and 55% were positive for E. coli with reduced susceptibility for cefotaxime. From the healthy and diarrheic cats, the estimated prevalence was respectively 0% and 25%. One diarrheic cat was positive for both reduced susceptible E. coli and P. mirabilis. The ESBL/AmpC genes found in this study were mainly blaCTX-M-1, but also blaCTX-M-14, blaCTX-M-15, blaTEM-52-StPaul, blaSHV-12 and blaCMY-2 were detected. This pilot study showed that the prevalence of ESBL/AmpC producing Enterobacteriaceae in healthy and diarrheic dogs, and diarrheic cats was relatively high. Furthermore the genes found were similar to those found in isolates of both human and food producing animal origin. However, since the size of this study was relatively small, extrapolation of the data to the general population of cats and dogs should be done with great care.